Exploring changes in levels and patterns of physical activity in undergraduate medical and nursing students during the COVID-19 pandemic - Al-Hindawi, Ahmed; Kumar, Nitya; Gaynor, Declan (Frontiers in Public Health, 2022)
This study reports the physical activity (PA) levels among medical and nursing students at a university in Bahrain during the COVID-19 pandemic. Through self-selection sampling of an online survey, participants' data on general demographics, PA levels before and during the COVID-19 pandemic and reasons for PA changes were collected. From the 110 valid responses, 70 participants (63%) experienced a decrease in PA during the COVID-19 lockdown. Fear of contracting COVID-19 and lack of motivation were two significant reasons for reduced PA levels (p < 0.001) compared to those who did not experience a decrease in PA. Other factors significantly associated with reduced PA levels include living alone (p < 0.018) or with roommates (p < 0.006) compared to living with family. Having more time available was associated with positive changes to PA levels (p < 0.001). Significant differences in MET-min/week were seen between students who experienced increased PA (median of 1605 MET-min/week) compared to those who experienced a decrease (424 MET-min/week) or no change (1070 MET-min/week) in PA levels (p < 0.001). In conclusion, low PA levels are prevalent within medical and nursing students in Bahrain (51% reported < 600 MET-min/week), with 2 in 3 students reporting a decrease in PA levels during the COVID-19 pandemic. Support programs and strategies to increase engagement in PA within this population are warranted.